2017
DOI: 10.1097/scs.0000000000003122
|View full text |Cite
|
Sign up to set email alerts
|

Extra-Gingival Pyogenic Granuloma Displacing Teeth

Abstract: Pyogenic granuloma is a common cause of growth of soft tissue in the oral cavity, especially in the gingiva. It is mainly associated with local and chronic irritants besides hormonal changes during pregnancy. Here, the authors present an unusual patient of an extra-gingival pyogenic granuloma with large dimensions and displacing teeth arising in a male patient. This is an interesting patient to be reported due to its exacerbated and atypical clinical features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…These lesions can manifest as either sessile or pedunculated growths [ 3 ]. While radiological features are rarely observed, there have been isolated cases such as one documented by Ketelin Juliane Dal Pra et al [ 5 ], in which radiographs showed bone loss, particularly horizontal bone loss. Histologically, pyogenic granuloma is characterized by a significant infiltration of lymphocytes, plasma cells, and neutrophils within arterial regions demarcated by endothelial lining.…”
Section: Discussionmentioning
confidence: 99%
“…These lesions can manifest as either sessile or pedunculated growths [ 3 ]. While radiological features are rarely observed, there have been isolated cases such as one documented by Ketelin Juliane Dal Pra et al [ 5 ], in which radiographs showed bone loss, particularly horizontal bone loss. Histologically, pyogenic granuloma is characterized by a significant infiltration of lymphocytes, plasma cells, and neutrophils within arterial regions demarcated by endothelial lining.…”
Section: Discussionmentioning
confidence: 99%
“…The term "PG" or "granuloma pyogenicum" was stated by Hartzell in 1904. This non-neoplastic reactive lesion is commonly occurring in the oral cavity as a response to trauma, chronic local irritation, and hormonal disturbances (1). The term pregnancy tumor is also used when it occurs in pregnant women.…”
Section: Introductionmentioning
confidence: 99%